Kant’s Conceptions of the Feeling of Life and the Feeling of the Promotion of Life in Light of Epicurus’ Theory of Pleasure and the Stoic Notion of Oikeiôsis - Vatansever, Saniye (Studia Kantiana, 2023)
This paper shows the ways in which Kant’s notions of the feeling of life and the feeling of the promotion of life may be influenced by Epicurus’ theory of pleasure and the Stoic notion of oikeiôsis, respectively. Accordingly, getting a clear picture of Epicurus’ theory of pleasure and the Stoic notion of oikeiôsis will help us (i) understand why Kant introduces these notions in the third Critique and (ii) why he identifies aesthetic pleasure with the feeling of the promotion of life. As I will demonstrate, the feeling of life allows us to be conscious of the harmonious interaction of our faculties with each other while the feeling of the promotion of life allows us to be aware of the harmonious relationship between our faculties and nature. Hence, the feeling of the promotion of life indicates the well-being of the subject in its relation to its environment.